Pelatihan Proyek Kimia Terapan Pembuatan Sabun Cuci Piring Di Desa Rawa Sekip Kecamatan Kuala Cenaku Kabupaten Indragiri Hulu - RACHMAN PANCA PRIYANDA, ELZA (Universitas Mataram, 2024)
Dish soap is one of the products that are often used in everyday life. Making dish soap can be done independently by each individual to save costs. The purpose of this activity is to reduce the consumer value of the community and foster the entrepreneurial spirit of the community of Rawa Sekip Village, Kuala Cenaku District, Indragiri Hulu Regency through applied chemistry project training for making dish soap. The soap making process is carried out in 4 stages, namely: Preparation of tools and materials, mixing materials, stirring materials, and filling soap into bottles. The community is very enthusiastic in participating in community service activities with the value of togetherness and enthusiasm in every stage carried out in making dish soap